Child Care Practices and Nutritional Status of Under-Five Children in Tanzania: Evidence from Fishing Communities in Pangani District - Mtoi, Edna H; Nyaruhucha, Cornelio N. M (International Journal of Asian Social Science, 2019)
Undernutrition is still a public health problem in Tanzania despite national and global efforts in combating it. However, little availability of suitable data limits understanding of why the problem still persists. This chapter aimed at finding out the determinants of undernutrition among under-five children in Tanzania. Specifically, this paper assessed the influence of child care practices on nutritional status of under-five children focusing on local fishing communities in Pangani District. A sample of 355 under-five children was selected from households using systematic sampling method. Cross-sectional research design was employed to collect both anthropometric quantitative and qualitative data. ENA for SMART software version 2011 was used to generate indices for weight-for-height, height-for-age and weight-for-age. The findings confirm that under-nutrition is still a public health problem in Pangani as indicated by higher level of stunting (27.9%) and wasting (5.1%). Binary Logistic Regression was employed to assess the influence of individual characteristics of a child and care practices by mothers/care-takers on under-nutrition in children under-five. Place of delivery, delivery assistance, sex of a child, having siblings under-five, immunization status, essential ANC visits and exclusive breast feeding were the most important factors associated with under-nutrition. The findings call for collaborative action between Government, NGOs and the District Nutrition Officer on how to curb malnutrition in Pangani.